A because the formula is s^2h/3 and if you plug it in, it's A.
We can subtract the sum of the two trinomials by one of the trinomials.
(7x²-5x+4)-(3x²+2x-1)
Let's look at each part.
7x²-3x²=4x²
-5x-2x=-7x
4-(-1)=5
So, the trinomial should look like:
4x²-7x+5
So, C. 4x²-7x+5 is the other trinomial.
Answer:
x = 13.4
Step-by-step explanation:
Use the Pythagorean Theorem
a² + b² = c²
x² + 6.8² = 14.1²
x² = 14.1² - 6.8²
x² = 152.57
Take the square root of both sides
x = 12.3519229272
Rounded
x = 13.4